Pengaruh Humas Pemerintah Dalam Program Rumah Umum Tidak Layak Huni Terhadap Citra Pemerintah - Nabilah Puteri Azzahra; Sa’adiyah El Adwiyah; Nani Nurani Muksin (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Based on development priorities, the city government repairs uninhabitable houses into habitable houses for people who cannot meet the physical needs of habitable houses in their socio-economic environment. So, the South Tangerang City Government is implementing a program to build Uninhabitable Public Houses (RUTLH). This research aims to determine how much influence government public relations has in the RUTLH development program on the image of the South Tangerang City government. The main theory used in this research is the government public relations theory according to Cutlip, Center and Broom (2015:5-6), then the South Tangerang City Government Image theory according to Kanaidi (2010:33). The data collection technique was carried out by distributing questionnaires to 40 respondents who had been counted. Sampling used the Stratifight Random Sampling Technique. This research is shown by the average value of respondents' answers for variable (X) of 3.27, this value is classified as high (Agree) and the average value of respondents' answers to variable (Y) is 3.14 which is also predominantly high (Agree). The considerable influence of Government Public Relations and the Image of the South Tangerang City Government can also be seen from the (R) correlation value of 0.759 which is said to be high or strong and the R Square value of 0.576 or 57.6% is influential while the remaining 42.4% is influenced by other things. .